Another look at boredom in language instruction: The role of the predictable and the unexpected - Kruk, Mariusz; Pawlak, Mirosław; Zawodniak, Joanna (Studies in Second Language Learning and Teaching, 2021)
Although recent years have seen a growing interest in positive emotions in second or foreign language learning and teaching, negative emotions are always present in the classroom and they deserve to be investigated in their own right. The article focuses on boredom, a construct that has been explored in educational psychology but has received only scant attention from second language acquisition researchers. It reports a study which examined the changes in the levels of boredom experienced by 13 English majors in four EFL classes and the factors accounting for such changes. Using data obtained from a few different sources (i.e., boredom grids, narratives, interviews, class evaluations and lesson plans), it was found that although boredom can be attributed to different constellations of factors, it was mainly traced to repetitiveness, monotony and predictability of what transpired during a particular class.